AFIKS-AFIKS DERIVASI BAHASA INGGIS DAN BAHASA TALAUD DIALEK NANUSA (SUATU ANALISIS KONTRASTIF) - ULALU, YUSSEKEN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT Â This research entitled â€œAfiks-Afiks Derivasi Bahasa Inggris dan Bahasa Talaud Dialek Nanusa (Suatu Analisis Kontrastif)â€, aims at describing and analyzing the derivational affixes in English and Talaud language Nanusaâ€Ÿs dialect in term of form, function, and meaning in verb, noun, adjective and adverb. The objectives of this research is to find similarities and differences of derivational affixes in English and Talaud language Nanusaâ€Ÿs dialect by using William Oâ€ŸGradyâ€Ÿs (1987) theory and contrasting by using Ladoâ€Ÿs method. Â This research used descriptive method. The data for English derivational affixes were collected from English textbook, namely ContemporaryÂ  Linguistic Analysis : An Introduction (1987) by Oâ€ŸGrady and for Talaud language Nanusaâ€Ÿs dialect were taken from four native speakers as informants who were born and lived in Mamahan village, Talaud island. Â The results of this research show either English or Talaud language Nanusaâ€Ÿs dialect has affixes of verb, noun, adjective and adverb derivation. Derivational affixes process in English through prefixes and suffixes while in Talauud language Nanusaâ€Ÿs dialect through prefixes, infixes, suffixes and confixes. Â Both English and Talaud language Nanusaâ€Ÿs dialect have derivational prefixes which have negative meaning. In context of proffesion or job, English derivational affixes process through suffixation; meanwhile, Talaud language Nanusaâ€Ÿs dialect through infixation. Â Key Words : Derivational Affixes of English, Talaud language Nanusaâ€Ÿs dialect,Â Â  Contrastive Analysis